Diet of Antarctic fur seals Arctocephalus gazella at the Danco Coast, Antarctic Peninsula - Casaux, Ricardo Jorge; Baroni, Paola Andrea; Ramon, Analia Ines (Polar Biology)
The diet of non-breeding male Antarctic fur seals, Arctocephalus gazella, was investigated at the Danco Coast, Antarctic Peninsula, by the analysis of 31 and 149 scats collected from January to March 1998 and 2000, respectively. Overall, fish and krill, followed by penguins and squids, were the most frequent prey and constituted the bulk of the diet. The importance of the remaining taxa represented in the samples (octopods, gastropods, bivalves, isopods, polychaetes and poriferans) was negligible. Among fish, channichthyids constituted the bulk of the diet, with Chionodraco rastrospinosus and Chaenodraco wilsoni, followed by the nototheniid, Pleuragramma antarcticum, being the main prey. The myctophid, Electrona antarctica, was the most frequent and numerous fish prey. The results are discussed and compared with those reported for the South Shetland Islands, the closest area for which similar information is available. Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Baroni, Paola Andrea. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina Fil: Ramon, Analia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata; Argentina